2021
DOI: 10.3390/plants10081647
|View full text |Cite
|
Sign up to set email alerts
|

Reading between the Lines: RNA-seq Data Mining Reveals the Alternative Message of the Rice Leaf Transcriptome in Response to Heat Stress

Abstract: Rice (Oryza sativa L.) is a major food crop but heat stress affects its yield and grain quality. To identify mechanistic solutions to improve rice yield under rising temperatures, molecular responses of thermotolerance must be understood. Transcriptional and post-transcriptional controls are involved in a wide range of plant environmental responses. Alternative splicing (AS), in particular, is a widespread mechanism impacting the stress defence in plants but it has been completely overlooked in rice genome-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 101 publications
(197 reference statements)
0
19
0
Order By: Relevance
“…RTD is the major backbone for accurate gene quantification of RNA-seq data analysis and consists of a list of genes and possible transcript isoforms of an organism ( Brown et al, 2017 ; Zhang et al, 2017a ; Rapazote-Flores et al, 2019 ; Vitoriano et al, 2021 ). The quality of the transcriptome annotation could help with fast and accurate estimation of transcript expression and AS events using the RNA-seq data with the help of the 3DRNA-seq tool ( Chaudhary and Kalkal, 2021 ; Guo et al, 2021 ; Vitoriano et al, 2021 ; Escudero-Martinez et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RTD is the major backbone for accurate gene quantification of RNA-seq data analysis and consists of a list of genes and possible transcript isoforms of an organism ( Brown et al, 2017 ; Zhang et al, 2017a ; Rapazote-Flores et al, 2019 ; Vitoriano et al, 2021 ). The quality of the transcriptome annotation could help with fast and accurate estimation of transcript expression and AS events using the RNA-seq data with the help of the 3DRNA-seq tool ( Chaudhary and Kalkal, 2021 ; Guo et al, 2021 ; Vitoriano et al, 2021 ; Escudero-Martinez et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…RTD is the major backbone for accurate gene quantification of RNA-seq data analysis and consists of a list of genes and possible transcript isoforms of an organism ( Brown et al, 2017 ; Zhang et al, 2017a ; Rapazote-Flores et al, 2019 ; Vitoriano et al, 2021 ). The quality of the transcriptome annotation could help with fast and accurate estimation of transcript expression and AS events using the RNA-seq data with the help of the 3DRNA-seq tool ( Chaudhary and Kalkal, 2021 ; Guo et al, 2021 ; Vitoriano et al, 2021 ; Escudero-Martinez et al, 2022 ). Despite rice being an important crop plant and several attempts being made in the past to improve its transcriptome annotation and AS diversity, IndicaRTD contains a significantly higher number of transcript isoforms ( Lu et al, 2010 ; Zhang et al, 2010 ; Zhang H. et al, 2019 ; Schaarschmidt et al, 2020 ; Wang S. et al, 2022 ; Hasan et al, 2022 ; He et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to understand the responses that allow plants to tolerate heat ( Janni et al, 2020 ). In response to heat stress (HS), plants undergo massive changes in the transcriptome, proteome, sugar levels, membrane composition and rate of photosynthesis ( Penfield, 2008 ; Zou et al, 2011 ; Su et al, 2018 ; Vitoriano and Calixto, 2021 ). Regarding the transcriptome, alternative splicing (AS) is a major gene-regulatory mechanism enhancing transcriptome and proteome diversity.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq is one of the most used techniques in biology, with a growing rate of around 3000 times in 6 years (2008)(2009)(2010)(2011)(2012)(2013)(2014) (Jazayeri et al, 2015). It has helped answer many biological questions and improve plant stress studies, growth and development analyses, and disease diagnosis (Vitoriano and Calixto, 2021;Marco-Puche et al, 2019). It also helps understand biological functions and mechanisms involved in plant adaptation, for example, as proven in a study of sweet potato where TF families including basic helix-loop-helix (bHLH), basic leucine zipper (bZIP), C2H2, C3H (Cys3His zinc finger), ethylene-responsive transcription factor (ERF), homo domain-leucine zipper, MYB (myeloblastosis), NAC (NAM (no apical meristem), ATAF1/2 (Arabidopsis transcription activation factor), CUC2 (cup-shaped cotyledon)), thiol-specific antioxidant, and WRKY domain (W, R, K, Y stand for amino acids tryptophan, arginine, lysine and tyrosine respectively) were disclosed involved in drought stress response (Arisha et al, 2020), and biodiversity as reported by nucleotide-binding site and leucine-rich repeats (NBS-LRR) resistance genes in walnut (Chakraborty et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It also helps understand biological functions and mechanisms involved in plant adaptation, for example, as proven in a study of sweet potato where TF families including basic helix-loop-helix (bHLH), basic leucine zipper (bZIP), C2H2, C3H (Cys3His zinc finger), ethylene-responsive transcription factor (ERF), homo domain-leucine zipper, MYB (myeloblastosis), NAC (NAM (no apical meristem), ATAF1/2 (Arabidopsis transcription activation factor), CUC2 (cup-shaped cotyledon)), thiol-specific antioxidant, and WRKY domain (W, R, K, Y stand for amino acids tryptophan, arginine, lysine and tyrosine respectively) were disclosed involved in drought stress response (Arisha et al, 2020), and biodiversity as reported by nucleotide-binding site and leucine-rich repeats (NBS-LRR) resistance genes in walnut (Chakraborty et al, 2016). A study on rice leaf response to heat stress identified 17 143 and 2162 heat response genes using RNA-seq data analyses of differential gene expression and differential alternative splicing, respectively (Vitoriano and Calixto, 2021). In another study differentially expressed genes involved in oil palm drought stress response were revealed to screen tolerant and susceptible oil palm plants (Jazayeri, 2015).…”
Section: Introductionmentioning
confidence: 99%